A Rational Route to Coordination Polymers with Condensed Networks and Cooperative Magnetic Properties1. Issue 15 (2nd September 2013) - Näther, Christian; Wöhlert, Susanne; Boeckmann, Jan; Wriedt, Mario; Jeß, Inke
Abstract In this report a rational route to coordination polymers that can show cooperative magnetic phenomena is presented. In this approach compounds based on transition metal cations, small sized terminal N‐bonded anionic ligands and additional neutral N‐donor co‐ligands are heated, which lead to the formation of intermediates, in which the metal cations are linked by the anionic ligands. Predominantly, the use of this method for the synthesis of bridged thio‐ and selenocyanato coordination compounds is described in this article but it can also be extended for the preparation of other compounds. In most cases the intermediates are formed in very pure form and in quantitative yields. Thus, compounds, which are not or at least very difficult to obtain, can be prepared if the synthesis is performed in solution. This is especially valid for thio‐ and selenocyanato coordination compounds, which mostly prefer terminal bonding instead of bridging coordination with less chalcophilic metal cations like e.g. MnII, FeII, CoII, or NiII. It is demonstrated how 1D and 2D networks can selectively be prepared and that this method is predestinated for the synthesis of compounds that show a slow relaxation of the magnetization. A large number of compounds were investigated in which the metal cation, the anionic ligand, or the neutral co‐ligand is exchanged, which allowed the study of structure‐property relationships. Further investigation showed that these reactions can proceed via several different intermediates. At first glance one disadvantage of this approach might be that the intermediates isolated consist of microcrystalline powders, which structurally are difficult to characterize. However, different possibilities are presented to overcome this problem including investigations of analogous compounds based on diamagnetic cadmium cations, which in contrast to the paramagnetic metal cations prefer a bridging coordination of the anionic ligands.